"That's Obviously Really Insensitive:" Attuning to Marginalization in a Parent-Teacher Encounter. Issue 2 (2nd April 2020) - Chen, Grace A.
Abstract: This paper draws on Ahmed's construct of affective economies to explore the role of affect in explaining how marginalization becomes (re)produced in pre-service teachers' encounters with an actor playing a Kurdish refugee mother in a simulated parent-teacher conference. Through an interpretive case study of four matched-pair pre-service teachers, this paper argues that affective explanations can complement an ideological perspective on marginalization. It does so by attending to the systemic production of marginalization and to the historicized selves and attunements of both pre-service teachers and the actor, and by illustrating the opportunities afforded for reproduction or resistance in particular encounters. The affective approach offers alternate entry points for teacher educators interested in the development of justice-oriented pre-service teachers.